Analisis Fungsi dan Signifikansi Perjanjian Hukum dalam Transaksi Perdagangan Internasional - Z. N, Nabilah; R. A., Haq,; T. C, Sihotang; S, Stephanie; A, Khairunnisa (Media Hukum Indonesia (MHI), 2025)
Legal agreements have a strategic role in supporting international trade transactions, especially in ensuring legal certainty, regulating the rights and obligations of the parties, and preventing disputes. This study analyzes the function, significance, and challenges of implementing legal agreements in cross-border transactions. With a normative legal approach, this study examines various regulations, principles of international law, and relevant case studies. The findings show that legal agreements not only provide legal certainty, but also play a role in managing business risks, resolving disputes efficiently, and creating stability in trade relations. Case examples show the importance of drafting comprehensive agreements and harmonizing international law to overcome differences in legal systems between countries. The implications of this study are the need for better education and understanding among business actors regarding the implementation of legal agreements. In addition, practical recommendations are provided to improve the effectiveness of legal agreements in promoting global economic stability. By understanding and implementing legal agreements effectively, business actors can avoid the risk of disputes, facilitate transactions, and build more solid and profitable business relationships.